A method for finding well-dispersed subsets of non-dominated vectors for multiple objective mixed integer linear programs - Sylva, John; Crema, Alejandro (European journal of operational research, 2007)
We present an algorithm for generating a subset of non-dominated vectors of multiple objective mixed integer linear programming. Starting from an initial non-dominated vector, the procedure finds at each iteration a new one that maximizes the infinity-norm distance from the set dominated by the previously found solutions. When all variables are integer, it can generate the whole set of non-dominated vectors.